2000
DOI: 10.1093/intimm/12.3.353
|View full text |Cite
|
Sign up to set email alerts
|

The origin of anti-nuclear antibodies in bcl-2 transgenic mice

Abstract: bcl-2 transgenic mice develop anti-double-stranded (ds) DNA antibodies similar to those present in systemic lupus erythematosus. To begin to understand where a breakdown in the regulation of autoreactive lymphocytes is occurring, we have used a bcl-2 transgene (Tg) in conjunction with an Ig Tg that allows us to identify and track anti-dsDNA B cells. Previously, we have shown that anti-dsDNA B cells are actively tolerized in BALB/c mice as manifested by their developmental arrest, follicular exclusion, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Thus, multiple factors are involved in the role of bcl-2 in tolerance, and these data indicate that regulated bcl-2 expression is not required for maintaining tolerance to Sm. This is similar to that observed for anti-DNA B cells in nonautoimmune mice (31).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, multiple factors are involved in the role of bcl-2 in tolerance, and these data indicate that regulated bcl-2 expression is not required for maintaining tolerance to Sm. This is similar to that observed for anti-DNA B cells in nonautoimmune mice (31).…”
Section: Discussionsupporting
confidence: 89%
“…A second possibility is that although BM-induced tolerance remains intact, there is a failure to regulate anti-dsDNA B cells produced in GCs. We have previously suggested that this is the case for bcl-2 Tg mice (34). Strikingly, in both lyn Ϫ/Ϫ and bcl-2 Tg mice, autoantibody production is reduced by the presence of the VH3H9 Tg.…”
Section: Maintenance Of the Anergic Phenotype In Lyn ϫ/ϫ Anti-dsdna Bmentioning
confidence: 83%
“…In animal models, the failure of lymphocyte apoptosis in promulgating disease pathogenesis is clearly illustrated in Bcl-2-transgenic mice (30) and Bim-deficient mice (31), both of which show evidence of SLE-like clinical symptoms caused by inappropriate survival of autoreactive lymphocytes. It has been postulated that disease in some patients with lupus may have a similar etiology, as elevated Bcl-2 expression in lymphocytes has been reported (32).…”
Section: Discussionmentioning
confidence: 99%